Binuclear copper coordination polymer material for electrocatalytic hydrogenation of membrane electrode and preparation method of binuclear copper coordination polymer material
Through the combination of dual-core copper coordination polymer material, non-precious metal-based anode and ion exchange membrane, the high cost of electrocatalytic hydrogenation materials and hydrogen evolution by-products are solved, and a high-efficiency and low-energy consumption acetylene hydrogenation reaction is achieved. Improves Faraday efficiency and selectivity of ethylene.
Patent Information
- Application Number
- CN202411461183.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-18
AI Technical Summary
Existing membrane electrode electrocatalytic hydrogenation materials are costly and are prone to produce hydrogen evolution by-products, which hinders its large-scale application and the selectivity of acetylene hydrogenation.
The dual-core copper coordination polymer material is prepared by hydrothermal method and metal post-modification method, combined with a non-precious metal-based anode and an ion exchange membrane, and assembled a film-forming electrode electrolytic cell to achieve high-efficiency electrocatalytic acetylene hydrogenation reaction.
The Faraday efficiency and acetylene conversion of ethylene are significantly improved at low energy consumption, and the generation of hydrogen evolution by-products is reduced, which is better than the performance of traditional flow cells and single-core adsorbed copper coordination polymer materials.
Smart Images

Figure CN119241862A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane electrode electrocatalytic materials, and in particular relates to a binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation and a preparation method thereof. Background Art
[0002] As an important raw material in the chemical industry, ethylene is currently produced mainly through high-temperature naphtha cracking process. Due to the limited oil reserves and low crude oil self-sufficiency rate in my country, there is an urgent need to find a method for producing ethylene that does not rely on oil. In view of my country's resource endowment of abundant coal and less oil, coal-to-acetylene (15 vol.%) and then acetylene hydrogenation to ethylene is a promising way to produce ethylene. In line with the national strategic goal of "carbon peak and carbon neutrality", the development of an electrocatalytic acetylene hydrogenation system using water as a hydrogen source has important application value for achieving green and clean development and high value-added utilization of coal-to-acetylene.
[0003] As the most common electrocatalytic acetylene hydrogenation reaction device at present, the liquid-phase flow electrolyzer has demonstrated good ethylene selectivity and current density. However, there are still problems that need to be solved, such as electrolyte overflow, gas diffusion layer blockage, high cell pressure and high energy consumption.
[0004] In contrast, no electrolyte passes through the cathode of the membrane electrode electrolyzer. The reaction gas with a certain humidity passes through the gas diffusion layer and directly reacts with the catalytic material to produce a gas-solid reaction, which effectively avoids the problems of electrolyte overflow and gas diffusion layer blockage. At the same time, the distance between the cathode and cathode in the membrane electrode electrolyzer is short, which can significantly reduce impedance losses, thereby reducing applied voltage and energy consumption. So far, the materials for membrane electrode electrocatalytic acetylene hydrogenation are mainly palladium-based materials, but their high cost hinders large-scale application; at the same time, palladium-based catalytic materials are easy to combine with active hydrogen, thereby producing hydrogen evolution byproducts, which reduces the selectivity of electrocatalytic acetylene hydrogenation.
[0005] To this end, the present invention considers it necessary to explore a new membrane electrode electrocatalytic hydrogenation material. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of existing membrane electrode electrocatalytic hydrogenation materials, such as high cost, easy generation of hydrogen evolution byproducts, and difficulty in large-scale application, and to provide a binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation and a preparation method thereof. Under industrial current, whether a flow-type electrolyzer or a membrane electrode electrolyzer is used, the material has excellent electrocatalytic acetylene hydrogenation performance and can effectively inhibit hydrogen evolution byproducts.
[0007] The concept of the present invention:
[0008] With an eye on reducing catalytic costs and the generation of hydrogen evolution byproducts, the present invention focuses its research direction on the research and development of non-precious metal hydrogenation catalytic materials, among which copper-based coordination polymer materials have the advantages of polymer materials such as high porosity, abundant raw materials and good gas adsorption, and can combine the moderate affinity of copper sites for active hydrogen, which is expected to reduce catalytic costs while avoiding hydrogen evolution byproducts. It is worth noting that the research team of the present invention found in the research and development process that binuclear copper sites have electronic properties different from those of mononuclear copper sites, which are more conducive to enhancing electron donation and acceptance to promote acetylene activation and semi-hydrogenation. Therefore, the present invention intends to use binuclear copper coordination polymer materials as the construction of membrane electrode electrocatalytic hydrogenation materials with both high activity (i.e., low cell pressure) and high selectivity.
[0009] Based on the above invention concept, in order to achieve the invention purpose, the technical solution provided by the present invention is:
[0010] A method for preparing a binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation is characterized in that it comprises the following steps:
[0011] 1) Weighing a dicarboxyl-containing imidazole salt and a copper salt, adding an organic solvent A thereto, stirring and ultrasonicating them to fully disperse them, to obtain a mixed solution;
[0012] The mixed solution is transferred to a reactor for hydrothermal reaction, after the reaction is completed and cooled to room temperature, the reaction product is rinsed and filtered under reduced pressure for multiple times, and then the filtered solid is dried to obtain a mononuclear copper coordinated polyimidazole salt;
[0013] 2) dispersing the mononuclear copper coordinated polyimidazole salt and copper salt obtained in step 1) in an organic solvent B, stirring and reacting under inert gas and alkaline conditions, coordinating with copper by a metal post-modification method, eluting and centrifuging the reaction product multiple times after the reaction, and then drying the solid after centrifugation to obtain a binuclear copper coordinated polymer material;
[0014] The base used in the alkaline condition is 1,8-diazabicyclo[5.4.0]undec-7-ene, potassium carbonate or potassium tert-butoxide.
[0015] Further, in step 1), the dicarboxyl-containing imidazole salt is any one of 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazole salt, 1,3-bis[(4-carboxyl-3',5'-diisopropyl)biphenyl]-halogenated imidazole salt, 4,7-bis(4-carboxylphenyl)-1,3-dimethylbenzimidazole halide salt or 3-[(4,4'-dicarboxyl[1,1'-biphenyl]-2-yl)methyl]-1-methyl-1H-halogenated imidazole salt and its derivatives;
[0016] The copper salt is copper nitrate, copper halide or cuprous halide;
[0017] The organic solvent A is N,N-dimethylformamide, methanol, acetone, tetrahydrofuran or 1,4-dioxane;
[0018] The molar ratio of the dicarboxyl-containing imidazole salt to the copper salt is 1:1 to 1:1.5;
[0019] The dosage ratio of the raw material to the organic solvent A is 1:125-250, mmol / mL; the dosage of the raw material here refers to the total amount of the dicarboxyl-containing imidazole salt and the copper salt;
[0020] The temperature of the hydrothermal reaction is 120-160° C., and the reaction time is 24-48 hours.
[0021] Further, in step 2), the copper salt is copper nitrate, copper halide or cuprous halide;
[0022] The organic solvent B is tetrahydrofuran, methanol or acetone;
[0023] The molar ratio of the mononuclear copper coordinated polyimidazole salt to the copper salt is 1:1 to 1:1.5;
[0024] The dosage ratio of the raw material to the organic solvent B is 1:100-400, mmol / mL; the dosage of the raw material here refers to the total amount of the mononuclear copper coordinated polyimidazole salt and the copper salt;
[0025] The reaction temperature is 20-60°C and the reaction time is 24-48h;
[0026] The inert gas is nitrogen or argon.
[0027] At the same time, the present invention also provides a binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation prepared by the above-mentioned preparation method, and the use of the binuclear copper coordination polymer material as a hydrogenation material in membrane electrode electrocatalytic hydrogenation to prepare ethylene.
[0028] The molecular structure of the binuclear copper coordination polymer material is:
[0029]
[0030] The squares represent aromatic rings.
[0031] Based on the above application, the present invention provides a method for preparing ethylene by membrane electrode electrocatalytic hydrogenation, which is special in that it comprises the following steps:
[0032] S1. Weigh the binuclear copper coordination polymer material prepared by the aforementioned preparation method as a cathode electrocatalytic hydrogenation material, add a binder, and evenly disperse it in a volatile organic solvent C to obtain a cathode material slurry;
[0033] S2. The cathode material slurry obtained in S1 is evenly coated on the gas diffusion layer (to reach the required loading amount), and after being fully dried, it is used as a cathode for standby use, that is, the binuclear copper coordination polymer material is used as a cathode catalyst layer;
[0034] S3. Assemble the non-precious metal-based anode, the cathode obtained in S2 and the ion exchange membrane into a membrane electrode electrolyzer to carry out electrocatalytic acetylene hydrogenation reaction to produce ethylene.
[0035] Further, in S1, the adhesive is polytetrafluoroethylene emulsion, perfluorosulfonic acid resin emulsion or fluorocarbon resin emulsion;
[0036] The organic solvent C is a volatile organic solvent such as isopropanol, ethanol, methanol or acetone;
[0037] The material ratio of the binuclear copper coordination polymer material, the organic solvent C and the adhesive is 1-100:5-20:10-500 (mg:mL:μL).
[0038] Further, in S2, the cathode material slurry is evenly coated on the gas diffusion layer by a spraying method;
[0039] The gas diffusion layer is 5% polytetrafluoroethylene and is placed on a flat plate material. The material of the flat plate material is carbon fiber paper, carbon fiber woven cloth, non-woven fabric or carbon black paper.
[0040] Furthermore, in S3, the non-precious metal-based anode is prepared by growing non-precious metal-based particles or their alloys, oxides, hydroxides, and composites on the anode current collector by impregnation or electrodeposition, that is, the non-precious metal-based material is used as the anode catalyst layer; the non-precious metal is Fe, Co, or Ni;
[0041] The anode current collector is nickel foam, copper mesh, titanium felt, carbon paper or carbon cloth, etc.;
[0042] The wet acetylene raw material used is pure acetylene or a mixture of acetylene and other gases (such as inert gas or ethylene); the flow rate of the wet acetylene raw material used is 5 to 1000 sccm;
[0043] The anolyte used is an acidic, neutral or alkaline liquid electrolyte or solid electrolyte, such as: 0.01 to 5M hydrochloric acid, 0.01 to 5M sulfuric acid, 0.01 to 5M KCl solution, 0.01 to 10M KHCO3 solution or 0.01 to 10M KOH solution; the flow rate of the anolyte used is 5 to 200 sccm.
[0044] Furthermore, in S3, wet acetylene raw material enters from the gas channel inlet of the cathode, and the corresponding product is collected from the gas channel outlet; at the same time, a peristaltic pump is used to promote the circulation of the anode electrolyte in the anode channel.
[0045] Principle of the present invention:
[0046] The present invention first uses a dicarboxyl-containing imidazole salt as a ligand, and uses a hydrothermal method to directly react the carboxyl group in the ligand with a copper salt to generate a mononuclear copper coordinated polyimidazolate, and then introduces a copper site through a metal post-modification method to successfully prepare a binuclear copper coordination polymer material. The binuclear copper coordination polymer material has electronic properties different from those of the mononuclear copper site, is more conducive to enhancing the electron donation and acceptance effect to promote the activation and semi-hydrogenation of acetylene, and has excellent membrane battery electrocatalytic hydrogenation performance, so it can be used as a catalytic hydrogenation material.
[0047] Advantages of the present invention:
[0048] 1. The present invention uses dicarboxyl-containing imidazole salt as a ligand and successfully prepares a binuclear copper coordination polymer material through a hydrothermal method and a metal post-modification method. The material has excellent membrane cell electrocatalytic hydrogenation performance and can realize efficient electrocatalytic acetylene to ethylene in a membrane electrode electrolyzer.
[0049] 2. The present invention uses the obtained binuclear copper coordination polymer material as the cathode catalyst layer, and uses the non-precious metal-based material as the anode catalyst layer, and assembles it into a membrane electrode electrolyzer with a gas diffusion layer and an ion exchange membrane to test the electrocatalytic acetylene hydrogenation performance. The test results show that when simulating the coal-to-acetylene gas flow (15 vol.%), the binuclear copper coordination polymer material can achieve 81.3% ethylene Faraday efficiency and 81.4% acetylene conversion rate at 0.7A current ( Figure 4 ). The membrane electrode electrocatalytic energy consumption of this material is not only lower than that of the traditional flow cell electrocatalytic energy consumption, but also exceeds the membrane electrode electrocatalytic acetylene hydrogenation performance of the currently reported membrane electrode materials and mononuclear adsorbed copper coordination polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 Schematic diagram of membrane electrode electrolysis cell.
[0051] Figure 2 Schematic diagram of the synthesis of binuclear copper coordination polymer materials (copper nitrate is used as the copper salt).
[0052] Figure 3 Schematic diagram of the synthesis of binuclear copper coordination polymer materials (the dicarboxyl-containing imidazole salt is 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazole salt, and the copper salt is copper nitrate).
[0053] Figure 4 This is a scanning electron microscope (SEM) photograph of the binuclear copper coordination polymer material.
[0054] Figure 5 For binuclear copper coordination polymer materials in membrane electrode electrolysis cells (catalytic reaction area: 4cm2 ) at different current densities on the product Faraday efficiency and acetylene conversion rate distribution diagram (15 vol.% acetylene mixed gas flow rate: 60 sccm). DETAILED DESCRIPTION
[0055] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:
[0056] The present invention provides a binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation and a preparation method thereof. Using dicarboxyl-containing imidazole salt as a ligand, a binuclear copper coordination polymer catalytic material is synthesized by a hydrothermal method and a metal post-modification method, the catalytic material is uniformly dispersed in a solvent to prepare a slurry of a certain concentration, and uniformly coated on a gas diffusion layer as a cathode electrode, and a non-precious gold-based material (such as NiFeCo 0.5 -LDH / Ni, NiFeCo 0.5 -LDH / Ti, IrO x / Ti, etc.) as the anode electrode, and the ion exchange membrane as the cathode and anode diaphragm, which are assembled together to form a membrane electrode electrolyzer reaction device. Figure 1 Schematic diagram of membrane electrode electrolysis cell.
[0057] In the step of synthesizing the mononuclear copper coordinated polyimidazole salt, the dicarboxyl-containing imidazole salt includes but is not limited to 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazole salt, 1,3-bis[(4-carboxyl-3',5'-diisopropyl)biphenyl]-halogenated imidazole salt, 4,7-bis(4-carboxylphenyl)-1,3-dimethylbenzimidazole halide salt, 3-[(4,4'-dicarboxyl[1,1'-biphenyl]-2-yl)methyl]-1-methyl-1H-halogenated imidazole salt and its derivatives, etc.; the copper salt used includes but is not limited to copper nitrate, copper halide and cuprous halide, and the solvent used (organic solvent A) includes but is not limited to N,N-dimethylformamide, methanol, acetone, tetrahydrofuran and 1,4-dioxane.
[0058] In the synthesis step of binuclear copper coordination polymer materials, inert gases include but are not limited to nitrogen and argon; the bases used include but are not limited to: 1,8-diazabicyclo[5.4.0]undec-7-ene, potassium carbonate, potassium tert-butoxide, etc.; the good solvents (organic solvent B) used include but are not limited to: tetrahydrofuran, methanol, acetone, etc.; the copper salts used include but are not limited to: copper halide, cuprous halide, copper nitrate, etc.
[0059] The adhesive includes but is not limited to polytetrafluoroethylene emulsion, perfluorosulfonic acid resin emulsion, fluorocarbon resin emulsion, etc.; the solvent (organic solvent C) used to prepare the slurry includes but is not limited to isopropanol, ethanol, methanol, acetone and other volatile organic solvents.
[0060] The gas diffusion layer is 5% polytetrafluoroethylene, which is placed on a flat plate material. The material of the flat plate material is carbon fiber paper, carbon fiber woven cloth, non-woven fabric or carbon black paper.
[0061] The anode current collector includes but is not limited to nickel foam, copper mesh, titanium felt, carbon paper, carbon cloth, etc.
[0062] The catalytic reaction area of the membrane electrode electrolyzer is mainly 1×1cm 2 , 2×2cm 2 and 5×5cm 2 .
[0063] The anolyte used is an acidic, neutral, alkaline electrolyte or a solid electrolyte, including but not limited to: 0.01-5M hydrochloric acid, 0.01-5M sulfuric acid, 0.01-5M KCl solution, 0.01-10M KHCO3 solution or 0.01-10M KOH solution, etc.
[0064] The present invention provides a schematic diagram of the synthesis of a binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu), such as Figure 2 As shown (wherein the box represents an aromatic ring), the specific synthesis steps are as follows:
[0065] (1) 0.4 mmol of dicarboxyl-containing imidazole salt and 0.4 mmol of copper nitrate were added to 50 mL of N,N-dimethylformamide, stirred and ultrasonicated for a period of time to fully disperse them, and then transferred to a hydrothermal reactor for hydrothermal reaction at 120°C for 24 hours. After the reaction was completed and cooled to room temperature, the reaction product was rinsed multiple times with a good solvent and vacuum filtered. The filtered solid was then placed in an oven at 60°C for overnight drying to obtain a mononuclear copper coordinated polyimidazole salt (Cu(Bcpi)).
[0066] (2) 20 mg of mononuclear copper coordination polyimidazole salt, 3 mg of potassium tert-butoxide and 10 mg of copper chloride were added to 5 mL of anhydrous methanol and reacted at room temperature for 24 h under the protection of inert gas. After the reaction was completed, the reaction product was rinsed and centrifuged multiple times with a good solvent, and then the solid after centrifugation was dried to obtain a binuclear copper coordination polymer material (Cu(Bcpi) / Cu).
[0067] Taking 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazole salt as an example of imidazole salt containing dicarboxyl group, the synthesis principle is as follows Figure 3 The SEM image of the prepared binuclear copper coordination polymer catalytic material is shown in Figure 4 shown.
[0068] The present invention provides a method for preparing the cathode electrode:
[0069] Accurately weigh a certain mass (1-100 mg) of binuclear copper coordination polymer catalytic material, add a certain volume (5-20 mL) of solvent and a certain volume (10-500 μL) of adhesive solution, then ultrasonicate for 30-60 seconds and magnetically stir for 30-60 minutes to obtain a uniform catalyst slurry; accurately measure a certain volume (5-10 mL) of catalyst slurry, load it on a material with a gas diffusion layer in the form of spraying, and obtain a cathode electrode after sufficient drying.
[0070] The present invention provides a method for preparing the above-mentioned anode electrode:
[0071] (1) Electrochemical deposition method: The current collector is used as the working electrode, and a mixed solution containing non-precious metal ions such as nickel, iron and cobalt is used as the electrolyte;
[0072] Using Ag / AgCl or Hg / HgO as reference electrode, a three-electrode system was used with a current of 10 mA / cm 2 The current density is set to be electrodeposited on the current collector for a certain period of time (6 to 60 minutes) to obtain Fe, Co, Ni and other non-precious metal-based particles or their alloys, oxides, hydroxides and composites grown on the current collector.
[0073] (2) Immersion and thermal decomposition method: First, clean the current collector with acetone / water, and then etch it in a 6M HCl solution for 30 minutes. Subsequently, the etched current collector is immersed in a mixed solution containing isopropanol (9mL), 6M HCl (1mL) and a certain concentration of non-precious metal precursor salt. After drying with an infrared lamp, the above current collector is calcined at 500°C for 20 minutes. Repeat the above immersion and thermal decomposition steps to obtain non-precious metal-based particles such as Fe, Co, Ni or their alloys, oxides, and composites grown on the current collector.
[0074] The present invention provides a method for testing the electrocatalytic acetylene hydrogenation performance of the membrane electrode electrolyzer:
[0075] (1) Using a membrane electrode electrolyzer, a gas diffusion electrode loaded with binuclear copper coordination polymer material is used as the cathode, and an ion exchange membrane and a non-precious metal-based anode (such as NiFeCo 0.5 -LDH / Ni, NiFeCo 0.5 -LDH / Ti, IrO x / Ti, etc.) to form the membrane electrode.
[0076] (2) Pure acetylene of a certain humidity or a mixture of acetylene and other gases (inert gas, ethylene, etc.) enters from the gas channel inlet of the cathode, and the corresponding products are collected from the gas channel outlet; at the same time, a peristaltic pump is used to promote the circulation of the anode electrolyte in the anode channel.
[0077] (3) During the reaction, the gas flow rate of the wet gas raw material is 5 to 1000 sccm; the flow rate of the anode electrolyte is 5 to 200 sccm.
[0078] (4) The electrocatalytic acetylene hydrogenation performance of the obtained catalytic material is evaluated using a DC regulated power supply; and the content of each gas phase product is detected using an online gas chromatography.
[0079] [Example 1]
[0080] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 1cm 2 ).
[0081] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0082] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0083] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.8 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0084] [Example 2]
[0085] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 1cm 2 ).
[0086] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0087] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0088] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.5 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0089] [Example 3]
[0090] (1) When 1,3-bis[(4-carboxyl-3',5'-diisopropyl)biphenyl]-imidazolium halide is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ti was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 1cm 2 ).
[0091] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0092] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0093] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.8 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0094] [Example 4]
[0095] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ti was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 1cm 2 ).
[0096] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0097] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0098] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.6 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0099] [Example 5]
[0100] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ti was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 1cm 2 ).
[0101] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0102] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0103] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.5 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0104] [Example 6]
[0105] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and IrO x / Ti was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 1cm 2 ).
[0106] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0107] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0108] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.7 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0109] [Example 7]
[0110] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and IrO x / Ti was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 1cm 2 ).
[0111] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0112] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0113] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.5 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0114] [Example 8]
[0115] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 4 cm 2 ).
[0116] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0117] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0118] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 1 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0119] [Example 9]
[0120] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 4 cm 2 ).
[0121] (2) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0122] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0123] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.7 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0124] [Example 10]
[0125] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 4 cm 2 ).
[0126] (2) The wet acetylene raw material used for the cathode is: 15 vol.% acetylene mixed gas. The gas flow rate of the mixed gas is controlled by a gas mass flow meter to be 40 sccm.
[0127] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0128] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.5 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0129] [Example 11]
[0130] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 4 cm 2 ).
[0131] (2) The wet acetylene raw material used for the cathode is: 15 vol.% acetylene mixed gas. The gas flow rate of the mixed gas is controlled by a gas mass flow meter to be 40 sccm.
[0132] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0133] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.3 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0134] [Example 12]
[0135] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 4 cm 2 ).
[0136] (2) The wet acetylene raw material used for the actual cathode is: 15 vol.% acetylene mixed gas. The gas flow rate of the mixed gas is controlled by a gas mass flow meter to be 60 sccm.
[0137] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0138] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.7 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0139] [Example 13]
[0140] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 4 cm 2 ).
[0141] (2) The wet acetylene raw material used for the actual cathode is: 15 vol.% acetylene mixed gas. The gas flow rate of the mixed gas is controlled by a gas mass flow meter to be 60 sccm.
[0142] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0143] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) was evaluated at a current of 0.5 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0144] [Example 14]
[0145] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 4 cm 2 ).
[0146] (2) The wet acetylene raw material used for the cathode is: 15 vol.% acetylene mixed gas. The gas flow rate of the mixed gas is controlled by a gas mass flow meter to be 100 sccm.
[0147] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0148] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material Cu(Bcpi) / Cu was evaluated at a current of 0.7 A. The content of each gas phase product at the gas chamber outlet was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0149] [Example 15]
[0150] (1) When 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazolium salt is used as the imidazolium salt containing a dicarboxyl group, the obtained binuclear copper coordination polymer catalytic material (Cu(Bcpi) / Cu) is loaded on a gas diffusion electrode as the cathode of the electrolytic cell, and NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 4 cm 2 ).
[0151] (2) The wet acetylene raw material used for the cathode is: 15 vol.% acetylene mixed gas. The gas flow rate of the mixed gas is controlled by a gas mass flow meter to be 100 sccm.
[0152] (3) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0153] (4) The electrocatalytic hydrogenation performance of the binuclear copper coordination polymer catalytic material Cu(Bcpi) / Cu was evaluated at a current of 0.4 A. The content of each gas phase product at the outlet of the gas chamber was detected using an online gas chromatography, and the Faraday efficiency of the product was calculated.
[0154] [Comparative Example]
[0155] (1) 20 mg of mononuclear copper coordination polyimidazole salt and 10 mg of copper salt were added to 5 mL of anhydrous solvent and reacted at room temperature for 24 h under the protection of inert gas. After the reaction was completed, the reaction product was rinsed and centrifuged multiple times with a good solvent, and then the solid after centrifugation was dried to obtain a mononuclear copper coordination polymer (Cu(Bcpi)-ACu) adsorbing copper as a comparison material.
[0156] (2) The gas diffusion electrode loaded with the above-mentioned Cu(Bcpi)-ACu was used as the cathode of the electrolytic cell, and the NiFeCo 0.5 -LDH / Ni was used as the anode of the electrolytic cell. The cathode and anode were separated by an anion exchange membrane. The anode electrolyte was 1M KOH solution. The electrolytic cell components were assembled into a membrane electrode electrolytic cell (catalytic reaction area: 1cm 2 ).
[0157] (3) The wet acetylene raw material used for the cathode is pure acetylene. The gas flow rate of pure acetylene is controlled at 60 sccm by a gas mass flow meter.
[0158] (4) The flow rate of the anolyte was controlled at 10 rpm using a peristaltic pump.
[0159] (5) The electrocatalytic hydrogenation performance of the copper coordination polymer catalytic material (Cu(Bcpi)-ACu) was evaluated using a DC regulated power supply. The content of each gas phase product at the gas chamber outlet was detected using an online gas chromatograph, and the Faraday efficiency of the product was calculated.
[0160] The specific evaluation results are shown in Table 1.
[0161] Table 1
[0162]
[0163]
[0164] As shown in Table 1: The membrane electrode PdCu / C material (ACS Appl. Mater. Interfaces, 2024, 16, 8668-8678) can obtain an ethylene Faraday efficiency of <75% at a current of 0.2A, while under the same acetylene atmosphere, the binuclear copper coordination polymer material (Cu(Bcpi) / Cu) obtained in the present invention exhibits a better ethylene Faraday efficiency at a higher current (0.6A~1A), while reducing the amount of precious metal Pd and optimizing the membrane electrode performance. It is worth mentioning that Cu(Bcpi) / Cu can achieve an ethylene Faraday efficiency of 88.2% at a current of 0.8A, which is not only better than the performance of the existing reported materials, but also significantly better than the ethylene Faraday efficiency (47.6%) of the mononuclear adsorbed copper coordination polymer material (Cu(Bcpi)-ACu) at the same current.
[0165] In addition, the present invention also prepares other binuclear copper coordination polymer materials according to the same method within the aforementioned process range, and applies them as hydrogenation materials in membrane electrode electrocatalytic hydrogenation to produce ethylene. They all have excellent electrocatalytic acetylene hydrogenation performance and can effectively inhibit hydrogen evolution by-products, meeting the needs.
[0166] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.
Claims
1. A method for preparing a binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation, characterized in that: The following steps are involved: 1) Weighing a dicarboxyl-containing imidazole salt and a copper salt, adding an organic solvent A thereto, stirring and ultrasonicating them to fully disperse them, to obtain a mixed solution; The mixed solution is transferred to a reactor for hydrothermal reaction, after the reaction is completed and cooled to room temperature, the reaction product is rinsed and filtered under reduced pressure for multiple times, and then the filtered solid is dried to obtain a mononuclear copper coordinated polyimidazole salt; 2) dispersing the mononuclear copper coordinated polyimidazole salt and copper salt obtained in step 1) in an organic solvent B, stirring and reacting under inert gas and alkaline conditions, eluting and centrifuging the reaction product several times after the reaction is completed, and then drying the solid after centrifugation to obtain a binuclear copper coordinated polymer material; The base used in the alkaline condition is 1,8-diazabicyclo[5.4.0]undec-7-ene, potassium carbonate or potassium tert-butoxide.
2. The method for preparing the binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation according to claim 1, characterized in that: In step 1), the dicarboxyl-containing imidazole salt is any one of 1,3-bis(4-carboxylic acid phenyl)-halogenated imidazole salt, 1,3-bis[(4-carboxyl-3',5'-diisopropyl)biphenyl]-halogenated imidazole salt, 4,7-bis(4-carboxylphenyl)-1,3-dimethylbenzimidazole halide salt or 3-[(4,4'-dicarboxyl[1,1'-biphenyl]-2-yl)methyl]-1-methyl-1H-halogenated imidazole salt and its derivatives; The copper salt is copper nitrate, copper halide or cuprous halide; The organic solvent A is N,N-dimethylformamide, methanol, acetone, tetrahydrofuran or 1,4-dioxane; The molar ratio of the dicarboxyl-containing imidazole salt to the copper salt is 1:1 to 1:1.5; The dosage ratio of the raw material to the organic solvent A is 1:125-250, mmol / mL; the dosage of the raw material here refers to the total amount of the dicarboxyl-containing imidazole salt and the copper salt; The temperature of the hydrothermal reaction is 120-160° C., and the reaction time is 24-48 hours.
3. The method for preparing a binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation according to claim 1 or 2, characterized in that: In step 2), the copper salt is copper nitrate, copper halide or cuprous halide; The organic solvent B is tetrahydrofuran, methanol or acetone; The molar ratio of the mononuclear copper coordinated polyimidazole salt to the copper salt is 1:1 to 1:1.5; The dosage ratio of the raw material to the organic solvent B is 1:100-400, mmol / mL; the dosage of the raw material here refers to the total amount of the mononuclear copper coordinated polyimidazole salt and the copper salt; The reaction temperature is 20-60° C., and the reaction time is 24-48 hours.
4. A binuclear copper coordination polymer material for membrane electrode electrocatalytic hydrogenation, characterized in that: It is prepared by any preparation method described in claims 1-3, and its molecular structure is: The squares represent aromatic rings.
5. Use of the binuclear copper coordination polymer material according to claim 4 as a hydrogenation material in membrane electrode electrocatalytic hydrogenation to produce ethylene.
6. A method for preparing ethylene by membrane electrode electrocatalytic hydrogenation, characterized in that: The following steps are involved: S1. Weigh the binuclear copper coordination polymer material prepared by any one of the preparation methods described in claims 1-3 as a cathode electrocatalytic hydrogenation material, add a binder, and evenly disperse it in a volatile organic solvent C to obtain a cathode material slurry; S2. The cathode material slurry obtained in S1 is evenly coated on the gas diffusion layer and fully dried as a cathode for standby use; S3. Assemble the non-precious metal-based anode, the cathode obtained in S2 and the ion exchange membrane into a membrane electrode electrolyzer to carry out electrocatalytic acetylene hydrogenation reaction to produce ethylene.
7. The method for preparing ethylene by membrane electrode electrocatalytic hydrogenation according to claim 6, characterized in that: In S1, the adhesive is polytetrafluoroethylene emulsion, perfluorosulfonic acid resin emulsion or fluorocarbon resin emulsion; The organic solvent C is isopropanol, ethanol, methanol or acetone; The material ratio of the binuclear copper coordination polymer material, the organic solvent C and the adhesive is 1-100:5-20:10-500 (mg:mL:μL).
8. The method for preparing ethylene by membrane electrode electrocatalytic hydrogenation according to claim 6 or 7, characterized in that: In S2, the cathode material slurry is evenly coated on the gas diffusion layer by spraying; The gas diffusion layer is 5% polytetrafluoroethylene and is placed on a flat plate material. The material of the flat plate material is carbon fiber paper, carbon fiber woven cloth, non-woven fabric or carbon black paper.
9. The method for preparing ethylene by membrane electrode electrocatalytic hydrogenation according to claim 8, characterized in that: In S3, the non-precious metal-based anode is prepared by growing non-precious metal-based particles or their alloys, oxides, hydroxides, and composites on the anode current collector by impregnation or electrodeposition; The anode current collector is nickel foam, copper mesh, titanium felt, carbon paper or carbon cloth; The wet acetylene raw material used is pure acetylene or a mixture of acetylene and other gases; the flow rate of the wet acetylene raw material used is 5 to 1000 sccm; The anode electrolyte used is 0.01-5M hydrochloric acid, 0.01-5M sulfuric acid, 0.01-5M KCl solution, 0.01-10M KHCO3 solution or 0.01-10M KOH solution; the flow rate of the anode electrolyte used is 5-200sccm.
10. The method for preparing ethylene by membrane electrode electrocatalytic hydrogenation according to claim 9, characterized in that: In S3, wet acetylene raw material enters from the gas channel inlet of the cathode, and the corresponding product is collected from the gas channel outlet; at the same time, a peristaltic pump is used to promote the circulation of the anode electrolyte in the anode channel.
Citation Information
Patent Citations
Azacyclocarbene metal coordination polymer and preparation method thereof, and application of azacyclocarbene metal coordination polymer as catalyst
CN106046057A
Bimetal site porphyrin N-heterocyclic carbene coordination polymer as well as preparation method and application thereof
CN117820657A
